Effect of rosemary and garlic oil supplementation on glutathione redox system of broiler chickens - Ancsin, Zsolt; Erdélyi, Márta; Mézes, Miklós (Acta Biologica Szegediensis, 2009)
The purpose of present study was to investigate the effect of rosemary and garlic oils on the lipid peroxidation and glutathione redox system in the blood and liver of broiler chicken. Day-old Hubbard broiler chickens (n=200) were fed with commercial broiler feed (control) and supplemented with garlic oil (0.25 g kg-1), rosemary oil (1.5 g kg-1) or their combination (0.25 g kg-1 garlic oil and 1.5 g kg-1 rosemary oil). At the end of the growing period (42 days of age) blood and liver samples of 10 animals were taken from each group to determine malondialdehyde and reduced glutathione content and glutathione peroxidase activity. There were no significant differences in the blood plasma or in red blood cell haemolysates among the groups, but garlic oil supplementation increased significantly reduced glutathione content and both essential oils the glutathione peroxidase activity in liver. However, combination of the two oils caused increase of malondialdehyde content of liver together with significantly higher glutathione peroxidase activity as compared to the control. Due to the beneficial effect on glutathione redox system both essential oils – used solely – can be used to reduce the effects of oxidative processes in physiological conditions.